Strategi Power Edukatif Kiai Pada Pengembangkan Iklim Organisasi Inklusif di Pesantren Al-Qodiri dan Pesantren Nurul Islam Jember - Moh. Dasuki (STAIFAS-Press, 2020)
The educative politics of the kiai with their power patterns are important in creating and creating an inclusive generation in pesantren. Therefore the kiai is the main figure in Developing the Organizational Climate. the purpose of this research is to find the Kiai's Educational Power Strategy in Developing an Inclusive Organizational Climate in Al-Qodiri Islamic Boarding School and Islamic Boarding School Nurul Jember. This type of research is qualitative with a case study approach designed with multi site. Data analysis used Miles and Huberman's Interactive Analysis Model which was carried out in two stages, namely single site analysis and cross-site analysis, while data wetness used source triangulation and member checks. The results of this study are First, the power of kiai is the identity of democratic and charismatic leadership, second, the source of power from the attitudes and principles of leadership, third, the basic power base of the family, education, moderate environment, cultural and structural activities of religious organizations, fourth, power capital. intellectual, emotional and spiritual, while the model consists of refrent power, persuasive power, power given by society, advice power, appreciative power and double connection power, fifth, power tactics through appreciation, facilitation, sharing and motivation while the control media uses monthly friendship forums and weekly gathering with close family and subordinates. Keywords: Power, Kiai, Inclusive Organizational Climate Politik edukatif kiai dengan pola powernya adalah hal penting dalam menciptakan dan mencetak generasi yang inklusif di pesantren. Oleh karena itu kiai sosok utama Pada Pengembangkan Iklim Organisasi tersebut. tujuan penelitian ini untuk Untuk menemukan Strategi Power Edukatif Kiai Pada Pengembangkan Iklim Organisasi Inklusif Di Pesantren Al-Qodiri Dan Pesantren Nurul Islam Jember.Jenis penelitian Kualitatif dengan pendekatan studi kasus yang dirancang dengan multi situs. Analisis data menggunakan Model Analisis Interaktif Miles dan Huberman yang dilakukan dua tahap yaitu analisis situs tunggal dan lintas situs sedangkan kebasahan data menggunakan trianggulasi sumber dan member cek. Hasil penelitian ini adalah Pertama, Kekuasaaan kiai merupakan jati diri kepemimpinan demokratis dan kharismatik, kedua, Sumber kekuasaan dari sikap dan prinsip kepemimpinannya,ketiga, Basis dasar kekuasaan dari keluarga,pendidikan, lingkungan moderat, aktivitas kutural dan struktural organisasi kegamaan,keempat, Modal kekuasaan intlektual, emosional dan spritual, sedangkan Modelnya terdiri refrent power, persuasif power, power given by society, advice power, apresiatif power dan Doble conection power,kelima, taktik kekuasaan melalui apresiasi, fasilitasi, sharing dan motivasi sedangkan media kontrolnya menggunakan forum silaturrahim bulanan dan silaturrahim mingguan bersama keluarga dekat dan bawahannya. Kata Kunci: Power, Kiai, Iklim Organisasi Inklusif